SYNTHESIS OF CARBOXYMETHYL DELONIX REGIA GUM USING NON AQUEOUS METHOD THROUGH OPTIMIZATION AND ITS CHARACTERIZATION. - A. Y. DHANDE,; R.Y. CHAUDHARI, (International Journal of Pharma and Bio Sciences, 2014)
Delonix regia gum (DRG) is a natural polysaccharide obtained from the endosperm of Delonix regia seeds, chemically classified as galactomannan. The objective of the present study was to derivatise DRG to carboxymethylated Delonix regia gum (CMDRG) using non aqueous method and to overcome limitations of natural polymer viz, fall in viscosity on storage, susceptible to microbial contamination, and to improve solution clarity. DRG was subjected to carboxymethylation using optimization technique (23 factorial design) by altering concentration of sodium chloroacetate (SCA), sodium bicarbonate and temperature of reaction mixture in presence of ethanol, while the degree of substitution (DS) and viscosity were selected as response variables. Optimized batch was characterized by the FTIR and differential scanning calorimetry. The X-ray diffraction study showed an amorphous nature in DRG and crystalline nature in CMCRG. The carboxymethylated Delonix regia gum (CMDRG) may provide an efficient alternative approach for the oral delivery of hydrophilic macromolecules.